1998
DOI: 10.1111/j.1528-1157.1998.tb01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Lobe Seizures as the Major Clinical Manifestation of Reversible Posterior Leukoencephalopathy Syndrome: Magnetic Resonance Imaging Findings

Abstract: Summary:Purpose: Reversible posterior leukoencephalopathy syndrome (RPLS) is an increasingly recognized brain disorder most commonly associated with malignant hypertension, toxemia of pregnancy, or the use of immunosuppressive agents. When associated with acute hypertension, RPLS typically occurs concurrently with the fulminant clinical syndrome of hypertensive encephalopathy. We describe occipital lobe seizures, in the setting of only moderate elevations of blood pressure, as the major clinical manifestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 30 publications
2
65
1
3
Order By: Relevance
“…The usefulness of FLAIR as compared with T2-weighted spin-echo MR imaging has been tested in a wide variety of brain diseases, including stroke [2,3], multiple sclerosis [4,5], infections [6,7], hypertensive encephalopathy/reversible posterior leukoencephalopathy syndrome [8], brain neoplasms [9,10,11], and hypoxic-ischemic encephalopathy [12].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of FLAIR as compared with T2-weighted spin-echo MR imaging has been tested in a wide variety of brain diseases, including stroke [2,3], multiple sclerosis [4,5], infections [6,7], hypertensive encephalopathy/reversible posterior leukoencephalopathy syndrome [8], brain neoplasms [9,10,11], and hypoxic-ischemic encephalopathy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many unrelated etiologies for this "syndrome" have been reported including hypertensive encephalopathy, glomerulonephritis with hypertension, eclampsia, and the use of immunosuppressive agents [1][2][3][4][5][6][7][8][9][10] (Table 1 [6] and progressive lupus while followed by multifocal seizures white matter of frontal and receiving prednisone and parieto-occipital lobes monthly cyclophosphamide bilaterally therapy studies in the 28 cases of RPLS reported in the literature showed increased T2 signal involving the white and, less consistently, gray matter with some predominance of the posterior portion of the cerebral hemispheres. Our patient became acutely confused, had visual hallucinations, generalized tonicclonic seizures and a MRI picture similar to the reported cases of RPLS.…”
mentioning
confidence: 98%
“…4,6,19 Other antiepileptics drugs can be used while considering the patient's coexisting medical disorders and prescribed drugs. 30 While long-term follow-up studies are limited, seizure recurrence or epilepsy appears to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…31 Although some case series report continuation of therapy for one to three months, phenytoin can probably be safely tapered as symptoms and neuroimaging findings resolve, usually after one to two weeks. 19 When recurrent, unprovoked seizures have occurred after recovery from an RPLS episode, it is reasonable to resume or initiate antiepileptic drug therapy. 29,31,32 Management of patients with PRES with Eclampsia being the underlying cause is different from that due to other causes.…”
Section: Discussionmentioning
confidence: 99%